Prompting second language writers for productive reflection using narrative questioning prompt - Nugrahenny Zacharias (Universitas Katolik Indonesia Atma Jaya, 2019)
This paper aims to introduce a novel form of reflective tool ‘narrative questioning’ to facilitate students’ elaborate and graded reflection in two ESL composition classes in a university in the US. Little has been written about a reflective tool where students need to produce a graded and elaborate reflection and this paper will seek to narrow that gap. Narrative questioning is developed primarily from Barkhuizen and Wette’s (2008) narrative frames. Narrative frames employ “a series of incomplete sentences and blank spaces of varying lengths” (Barkhuizen, 2014, p. 13). Narrative questioning utilizes a series of questions through which students reflected on their perceived learning gain throughout the semester. This paper will first discuss research in narrative reflective tools. Then, it will describe the classroom pedagogical lesson that I conducted to introduce and guide students to write their reflection using narrative questioning. Thirdly, the data gathered through students' reflection and individual interviews of 10 students will be presented and discussed. The data illustrates the different ways of narrative questioning facilitate reflection. Limitations of the narrative questioning elicited from students' interviews will also be presented here along with the pedagogical implication of the study.